Evaluation of anti-inflammatory and antidiabetic activity of ethanolic extracts of Desmodium pulchellum Benth. (Fabaceae) barks on albino wistar rats - Sadia Noor, S. M. Abdur Rahman, Zebunnesa Ahmed, Atanu Das, Md. Monir Hossain & (Journal of Applied Pharmaceutical Science, 2013)
Effects of ethanolic extract of Desmodium pulchellum Benth. (Fabaceae) barks on alloxan-induced diabetic rats were investigated. In diabetic rats, blood glucose levels were reduced by 18.64 – 34.04 % on consumption of the extracts, with greater effect exhibited by the 1000mg/kg extract whereas in Glibenclamide treated diabetic rats, blood glucose levels were reduced upto 73.55%. The results suggested ethanolic extract of barks may contribute to the reduction of blood glucose levels and can be useful in the management of diabetes. The acute oral toxicity showed that the ethanolic extract of D. pulchellum barks was safe until 4000mg/kg body weight and no macroscopical organ abnormalities were observed in acute oral models. The investigations on Albino (Wistar) rats at dosage of 100, 200 and 400 mg/kg of ethanolic extract of D. pulchellum barks were made for aniti-inflammatory action by using carrageenan induced paw edema and cotton pellete granuloma technique. The results of the study suggested significant dose dependent activity of extracts as compared to control group for both acute and chronic inflammation.
Keywords: Desmodium pulchellum barks, anti-